Kualitas Pelayanan Yang Berdampak Pada Kepuasan Pelanggan - Nova Sabrina; Muhammad Asrin Jazuli (Manajemen dan Bisnis, 2023)
This research aims to examine the influence of service quality dimension, namelytangible (physical evidence), reliability, responsiveness, assurance, and empathy,on the statisfaction of customers at the payment counters for electricity, water, andonline telephone services of Mitra Sumatera 008 Stabat. The population of this study consists of customers. The research sample consist of 30 respondents selectedusing Non- Probability sampling technique with an Accidental Sampling approach.This approach selects respondents based on chance encounters with the researcherand considered suitable to be included as samples. The analysis results indicatethat the indicators are valid and the variables are reliable, thus they can be used for further   analysis.   In   testing   the   classical   assumptions,   no   issues   ofmulticollinearity              (high correlation between independent variables).  heteroscedasticity (unequal residual variances), or non-normal distribution of residuals were found. This indicates that the regression model used satisfies the classical assumptions. Based on the research findings, it can be concluded that the dimension of service   quality,   namely   tangible, reliability,   responsiveness, assurance, and empathy, have a significant influence on the satisfaction of customers